2008
DOI: 10.1143/jpsjs.77sc.138
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Property of BaFe2As2Probed by75As NMR

Abstract: We report the detailed analysis of zero-external-field (ZF) 75 As nuclear-magnetic-resonance (NMR) measurement of the ternary iron arsenide BaFe2As2. The ZF 75 As-NMR spectrum clearly revealed that the magnetically ordered state is commensurate. Its internal magnetic field at the As site is 1.39(2) T. KEYWORDS: BaFe2As2, magnetic transition, nuclear magnetic resonanceThe discovery of superconductivity in F-doped LaFeAsO 1) has accelerated further investigations of the related superconductors.2-4) The common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…For all three compounds, we find that overall both Ts and TN are suppressed by pressure. On a gross level, this is therefore consistent with the general picture of the phase diagram of 122‐type iron‐based superconductors, [ 4,30,182–185 ] in which the application of pressure leads to a suppression of Ts and TN. However, on a finer level, the evolution of the splitting ΔT=TsTN (shown in the insets of Figure 6a–c) shows a more complicated behavior.…”
Section: Effect Of Hydrostatic Pressure On Superconductivity Magnetisupporting
confidence: 86%
See 1 more Smart Citation
“…For all three compounds, we find that overall both Ts and TN are suppressed by pressure. On a gross level, this is therefore consistent with the general picture of the phase diagram of 122‐type iron‐based superconductors, [ 4,30,182–185 ] in which the application of pressure leads to a suppression of Ts and TN. However, on a finer level, the evolution of the splitting ΔT=TsTN (shown in the insets of Figure 6a–c) shows a more complicated behavior.…”
Section: Effect Of Hydrostatic Pressure On Superconductivity Magnetisupporting
confidence: 86%
“…[ 15,181 ] It is thus of great importance to investigate the response of Ts and TN to a “clean” tuning parameter (i.e., hydrostatic pressure), which does not involve changing levels of disorder. Whereas the effect of pressure [ 4,30,182–185 ] is known to suppress Ts and TN and to induce superconductivity, the finer, more quantitative details of the phase diagram under pressure in terms of ΔT=TsTN were not elucidated. [ 186,187 ]…”
Section: Effect Of Hydrostatic Pressure On Superconductivity Magnetimentioning
confidence: 99%
“…12,13) The zero-field 75 As-NMR spectrum also revealed that the magnetically ordered state of this compound is commensurate. 14,15) The evaluated H int at 4.2 K decreases gradually with increasing pressure. 16) The results are consistent with the other group's NMR results obtained using single crystals.…”
mentioning
confidence: 99%
“…The obtained spectral profiles are basically the same as that of the parent material BaFe 2 As 2 . 14,15) By the same analytical procedure described in ref. 15, we evaluated the internal magnetic field H int at the As site to be 1.23 (5) T for x = 0.3 and 1.17(3) T for x = 0.4.…”
mentioning
confidence: 99%
See 1 more Smart Citation